Parallel Altars of Justice: Reimagining Kanzo and Ezili Fét in South Florida - Dennis, Dorcas (Journal of Africana religions, 2025)
This article examines ways Haitian Americans navigate discourses and systems of justice dispensation in addressing experiences of injustice and violence. Haitians in Miami who practice Vodou navigate two parallel systems as far as the discourse and dispensation of justice are concerned. One world is informed by Vodou discourses and practices and the other by the culture of the American legal and criminal justice system. The research considers the sociocultural roles Vodou priests (Oungans and Manbos) play in how the community navigates the two models of justice in the diaspora. Drawing on Kanzo and Ezili Fét, this article shows how the community negotiates issues of injustice, violence, and discrimination in ways that complement American systems of justice. This article involves fieldwork among members and their priestess (Manbo Ingrid Llera) at the Vodou Holistic Center in South Florida.